The art of Japanese ceramics - Mikami, Tsugio (Weatherhill, 1972)
Contents: 1. Japan in world geramic culture; 2. Geramics in Japanese Life; 3. The nature of Japanese Geramics; 4. Low-fire Pottery of the Prehistoric Age; 5. Early high-fired Geramics; 6. The six Ancient Kilns; 7. The flowering of Geramic art;...